TO WHAT EXTENT CAN A PUBLISHER OF AN OLD POLISH TEXT ALTER A TRANSCRIPTION? REFLECTIONS ON THE STORY OF THE “THREE INDIAS” IN "HISTORYJA TRZECH KROLI" (HISTORY OF THE THREE KINGS) - Ziółkowska, Olga (Prace Polonistyczne, 2025)
The article seeks to answer the question posed in the title: to what extent can a publisher intervene in the linguistic specificity of an Old Polish text. To explore this, editorial interventions to the most recent and, so far, only comprehensive edition of Historyja Trzech Kroli (History of the Three Kings) were analyzed, specifically focusing on three corrections in the section concerning the “three Indias”. Two of these alterations supplement words that are currently illegible due to physical damage to the manuscript, while the third one attempts to “repair” a problematic substantive, compositional, and source record, which, from our today’s perspective, seems damaged. The article highlights two clashing trends in the practice of publishing old texts: romantic idealism and editorial realism. The considerations are further contextualized in a Western European background.